2017
DOI: 10.5222/otd.2017.57625
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of zoledronic acid infusion in patients treated for postmenopausal osteoporosis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The results of the present study suggested that the absence of asymptomatic or unreported adverse effects such as renal failure and hypocalcemia. These findings support previous studies and suggest that ZA is a safe modality in the treatment of SRE among patients with cancer (3,23,24).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the present study suggested that the absence of asymptomatic or unreported adverse effects such as renal failure and hypocalcemia. These findings support previous studies and suggest that ZA is a safe modality in the treatment of SRE among patients with cancer (3,23,24).…”
Section: Discussionsupporting
confidence: 92%
“…However, most of ZA adverse effects were described as acute phase responses (25). These mainly included; pyrexia, musculoskeletal, gastrointestinal (GI), eye inflammation, and other general adverse effects (3,25,26). Additionally, ZA treatment resulted in significant changes in biochemical parameters such as serum calcium, phosphorus, and creatinine levels (23,24,27).…”
Section: Introductionmentioning
confidence: 99%